Sangre Grande land use plan - Government of the Republic Trinidad and Tobago. Ministry of Planning and Development. (Town and Country planning Division, 2011)
Presents the planning framework for the Sangre Grande area, a survey of the area, constraints and potential for development, and planning proposals.
Keywords: Urban planning - Trinidad and Tobago, Planning - Land use - Sangre Grande, Development planning - Sangre Grande, Land development, Physical planning, Socio-economic factors - Sangre Grande, Infrastructure - Sangre Grande, Housing - Sangre Grande